Motivation for participation of secondary school, students in sports and physical activities in Nigeria (2013)
The study was to examined different motivations for secondary school students' participation in sport and physical activities in Nigeria. A sample of 1,800 secondary school students from 60 public schools in Nigeria was studied to determine what motivated their participation in sports and physical activities. The sample was stratified across public schools in the six geo-political zones of the country and all students completed the Participation Motivation Questionnaire (PMQ) as well as Task and Ego Orientation in Sport Questionnaire (TEOSQ) with 0.79 and 0.84 respectively. The results revealed that the two achievement goal orientations were slightly but significantly correlated (r= . 18, p< . 01). Task orientation was most strongly related to skill development and team motives, whereas ego-orientation was related most clearly to status motives. Further, canonical correlation analysis showed skill development and team atmosphere incentives to be highly related to task-orientation Moreover, ego orientation was positively and highly correlated with status/recognition motives. Some 20.8% of the variance in participation motivation was explained by the two functions of achievement goal orientation. There were also significant sex differences in motivation to participate in sport activities for all students from the schools. Results of this study suggest that teacher, coaches, and others involved in the promotion of sport and physical activities with children and young people should promote intrinsic, self-determined forms of motivation, such as task orientation. It is therefore recommended that teachers should create a predominantly mastery climate that can be achieved by emphasising personal improvement, choice, and learning in sports and physical activities.